2007
DOI: 10.1007/s10750-006-0298-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of the polychaete Neanthes succinea in phosphorus regeneration from sediments in the Salton Sea, California

Abstract: The Salton Sea currently suffers from several well-documented water quality problems associated with high nutrient loading. However, the importance of phosphorus regeneration from sediments has not been established. Sediment phosphorus regeneration rates may be affected by benthic macroinvertebrate activity (e.g. bioturbation and excretion). The polychaete Neanthes succinea (Frey and Leuckart) is the dominant benthic macroinvertebrate in the Salton Sea. It is widely distributed during periods of mixing (winter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…In this study we manipulate both metrics (density and size) to investigate impacts of polychaetes on O 2 and nitrogen solute fluxes. Previous laboratory studies of nereid enhancement of solute fluxes reported results similar to ours, with relatively small densities and/or size of individuals in each treatment (Bartoli et al 2000, Christensen et al 2000, Swan et al 2007. One of these studies (Bartoli et al 2000) used A. succinea worms of a size similar to that used in our small worms treatment, and these authors found a remarkably similar linear relationship between animal biomass and denitrification (Fig.…”
Section: Effects Of Polychaete Biomass Versus Sizesupporting
confidence: 84%
See 1 more Smart Citation
“…In this study we manipulate both metrics (density and size) to investigate impacts of polychaetes on O 2 and nitrogen solute fluxes. Previous laboratory studies of nereid enhancement of solute fluxes reported results similar to ours, with relatively small densities and/or size of individuals in each treatment (Bartoli et al 2000, Christensen et al 2000, Swan et al 2007. One of these studies (Bartoli et al 2000) used A. succinea worms of a size similar to that used in our small worms treatment, and these authors found a remarkably similar linear relationship between animal biomass and denitrification (Fig.…”
Section: Effects Of Polychaete Biomass Versus Sizesupporting
confidence: 84%
“…These experimental abundances compare well with historical summer densities of polychaetes in the Choptank estuary, which range from ~500 to 4000 worms m −2 (Llanso et al 2010) and to the worm densities used in previous published experiments (e.g. Bartoli et al 2000, Swan et al 2007). Cores were then allowed to equilibrate over night in cylindrical tanks filled with estuarine water under continuous aeration and water circulation in a dark, temperature-controlled (25°C) chamber at ambient salinity (11.4).…”
Section: Effects Of Polychaete Abundance and Oxygen (Expt A-o)supporting
confidence: 82%
“…Some general prediction models of these processes have already been developed; however, in many cases unpredictable local factors are of great importance (Boström et al 1982, Pant and Reddy 2001, Wang et al 2003, KowalczewskaMadura and Gołdyn 2010. The most important factors influencing the release of phosphorus are: temperature (Kelderman 1984, Psenner 1984, Forsberg 1989, pH (Lijklema 1980, Boström et al 1988, Moore and Reddy 1994, the concentration of oxygen in the surface layer of sediments and in the near-water layer , Wiśniewski and Planter 1987, Ishikawa and Nishimura 1989, Uchmański et al 1993, Kleeberg and Dudel 1997, the concentration of Fe and Mn (Murphy et al 2001, Czerwieniec 2002, Søndergaard et al 2002, and bioturbation by macroinvertebrates (Andersson et al 1988, Tatrai 1988, Swan et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…The current lake was unintentionally created in 1905-1907, when the Colorado River flooded the Salton Basin for a period of 16 months. Profundal sediments are highly sulfidic, and sulfate reduction is suspected to be the dominant TEAP within these sediments (54). Based on elemental analysis (51) and 137 Cs activity (37) of sediment layers, a depth of ϳ22 cm marks the point when flooding of the Salton Basin occurred.…”
mentioning
confidence: 99%